Relação entre psicologia e fenomenologia a partir da obra "Psicologia e Fenomenologia" (1917) de Edmund Husserl - Barbieri, Josiane Beatriz Piccin (2011)
The relationship between Psychology and Phenomenology has been a relevant subject regarding the philosopher Edmund Husserl masterpiece (1859-1938), taking into account the Phenomenology founder and one of the representative thinkers of the XIX century which influenced his philosophical workflow at his time and also sciences in a general point of view. Psychology has been one of the most tackled subjects in his writings turning possible the foundation of a new flow, recognized as Phenomenological Psychology. The aim of such dissertation is to contribute with studies on phenomenology and it´s practical contrast in psychology side. From the work review‟s and analysis‟ ones furnished with the title Phenomenology and Psychology (1917), the aim is to have it in a brief writing from Husserl, in only one time, inside an introduction side to Phenomenology and also such method. This work begins by bringing up a critical discussion by Husserl to Psychologysm term used to detail philosophical positioning that would reduce the cognoscitive content to psychological mechanisms and phenomenon subject to the conscious concept and also introduce Husserl´s point of view in Psychology and Phenomenology. In order to define phenomenology it is focused in particular the phenomenon idea providing the adequate amplitude to it, by clarifying it sense inside the phenomenological view and relating it with the idea of an object . Phenomenon, in the phenomenological side it´s not about the truth as an object of nature and this is the aim of such study. In order to establish relations between phenomenon and object, Husserl takes back the conscience concept and it will provide the origin to two different sciences: conscience science itself and objective sciences in general. Once such characteristics are presented, the conscience science makes explicit its close relationship with psychology, especially when it comes to Husserl naming it as pure psychology . From such relation on, this work originates in the connection between psychology and transcendental personal nature of it. Finally, Husserl´s aim in phenomenology as a performer of this idea is logical psychology of phenomenology besides the opening of an enormous field in rational knowledge and, thus, not having the lighter, but a heavier weight on the chance of having empiric psychology knowledge taking place